Analysis of Student Misconceptions of Cell Material Using Four-Tier Diagnostic Test Instruments with the CRI Method at MA Darul Muqorrobin Kendal - Rodhiyah, Enni; Ismail, Ismail; Wijayanti, Erna (Bioeduca : Journal of Biology Education, 2024)
Biology learning is closely related to conceptual understanding. Incorrect understanding of students if not immediately corrected can lead to misconceptions. This study aims to analyze and identify the causes of students' misconceptions about cell material using a four-tier diagnostic test with the CRI method. This type of research is descriptive quantitative research. The population used was all students of class XI MA Darul Muqorrobin Kendal. The research subjects were 52 students using purposive sampling technique. Data collection techniques using tests, interviews, questionnaires and documentation. The results of the data analysis showed that the percentage of students who had misconceptions was 51%, understood the concept 22%, guessed 10% and did not understand the concept 17%. While the highest misconception for each sub material is 60% in protein synthesis. The percentage of factors that cause misconceptions from students is 60%, teachers are 44%, learning methods are 66%, teaching context errors are 48%, and textbooks are 40%. Based on the results of this analysis, misconceptions still often occur in cell material, so further research is needed on other materials.